Validated pre-discharge survey of patient satisfaction in orthopaedic care - Jain, Ravi Kant; Jain, Adhir; Jain, Neeraj (International Journal of Research in Orthopaedics, 2019)
Background: Worldwide, increasing concern has been given to the assessment of patient satisfaction survey as a method of monitor of the quality of health care provision in the health institutions. The study aimed to assess the level of patient satisfaction with preoperative and postoperative surgical services and its associated factors. Study includes Experience of 17 questionnaires. Methods: A total of 507 indoor patients were taken on a random basis full filing the inclusion and exclusion criteria, over a period of 1 year from December 2017 to January 2018. Firstly, we applied Cronbach’s alpha to know the reliability of survey questionnaire, then we collected the final data. Association between two non-parametric variables was seen using Pearson’s chi-square test. A p value of less than 0.05 was taken as statistically significant. Data was analysed using SPSS 21.0. Results: Patients with good satisfaction rates were 60.2%. We found that males are more satisfied then females with Pearson Chi-square value=8.033, df=1, p value=0.005. Patients with age of above 80 years and between age group of 21-40 years have comparatively lower satisfaction rates with Pearson Chi-square value=33.265, df=4, P value=0.000. Conclusions: Assessing patients’ satisfaction rates can be a simple and cost effective technique for evaluating the services provided by health care providers and institutions and should be conducted periodically to detect carelessness and bring about overall improvement in the quality of care provided. This should be generalised and universally accepted.